2010
DOI: 10.1016/j.cell.2009.12.033
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Energetic Mechanisms of Cooperative Autoinhibition and Activation of Vav1

Abstract: SUMMARY Vav proteins are guanine nucleotide exchange factors (GEFs) for Rho family GTPases. They control processes including T cell activation, phagocytosis and migration of normal and transformed cells. We report the structure and biophysical and cellular analyses of the five-domain autoinhibitory element of Vav1. The catalytic Dbl homology (DH) domain of Vav1 is controlled by two energetically coupled processes. The DH active site is directly, but weakly, inhibited by a helix from the adjacent Acidic domain.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
169
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(180 citation statements)
references
References 48 publications
8
169
1
1
Order By: Relevance
“…Our analysis suggests an inhibitory control of GEF1 activity by the SPn domain of TRIO. Consistent with these findings, the N terminus of TRIO has been shown to act as a dominant-negative inhibitor of TRIO's activity (21), and similar inhibitory mechanisms have been reported in other Dbl family proteins (22,23). Thus, despite its heterologous nature, the established mDISC1 genetic system has proven useful for studying DISC1's functions.…”
Section: Discussionsupporting
confidence: 56%
“…Our analysis suggests an inhibitory control of GEF1 activity by the SPn domain of TRIO. Consistent with these findings, the N terminus of TRIO has been shown to act as a dominant-negative inhibitor of TRIO's activity (21), and similar inhibitory mechanisms have been reported in other Dbl family proteins (22,23). Thus, despite its heterologous nature, the established mDISC1 genetic system has proven useful for studying DISC1's functions.…”
Section: Discussionsupporting
confidence: 56%
“…However, this hypothesis is unlikely because we did not detect an increase in Vav2 tyrosine phosphorylation upon Wnt stimulation. Alternatively and more likely, it is possible that the interaction frees the Vav2 catalytic Dbl homology domain from the coordinated auto-inhibition by the Acidic and Calponin homology domains (Yu et al, 2010). Thus, p120-catenin interaction would mimic the effects of Vav2 phosphorylation in the Acidic domain.…”
Section: Discussionmentioning
confidence: 99%
“…GEF activity of several RhoGEFs of the Dbl type is regulated by the intramolecular autoinhibition. For example, Vav, Dbl, Asef, Tim, and PDZRhoGEF are negatively regulated by their own N-terminal regions (21)(22)(23)(24)(25)(26). Our results demonstrated that the region containing amino acids 212-332 of ARHGEF10 is a negatively regulatory region for its GEF activity.…”
Section: Discussionmentioning
confidence: 99%